PH‐Buffer Contained Electrolyte for Self‐Adjusted Cathode‐Free Zn–MnO2 Batteries with Coexistence of Dual Mechanisms. Issue 11 (7th October 2021) - Liu, Zhexuan; Yang, Yongqiang; Liang, Shuquan; Lu, Bingan; Zhou, Jiang
Abstract : Aqueous Zn–MnO2 batteries have received much attentions for large‐scale applications because of high safety and low cost. However, the energy storage mechanisms of Zn–MnO2 system are still in dispute. Herein, a cathode‐free Zn–MnO2 battery is provided with the coexistence of dual mechanisms in mild acidic environment, in which the decisive guiding effect of the pH value in electrolyte on the mechanism is deeply investigated. On this basis, acetic acid (HAc) is used as a buffering additive to effectively suppress the "fluctuation" phenomenon during the operation, hence achieving the "self‐adjust" mechanism. The assembled soft package battery possesses a long lifetime of 2000 cycles with the Coulombic efficiency of 99.6%, improved high‐loading performance and rate capability. A new idea is provided for the exploration of energy storage mechanism of Zn–MnO2 battery as well as a guidance on the optimization strategies especially the battery construction. Abstract : Derived from the incomplete dissolution of MnO2 in the deposition/dissolution reaction, further investigation on the pH‐guided coexistence of dual mechanism is conducted. The relationship among the "sawtooth" variation of pH value in the electrolyte, ever‐changing mechanisms, and the "fluctuation" phenomenon during the operating is investigated. Furthermore, CH3 COOH (HAc) is used as pH‐buffer to alleviate corrosion and hydrogen evolution reaction.